2015
DOI: 10.3402/ejpt.v6.29126
|View full text |Cite
|
Sign up to set email alerts
|

Global mental health and trauma exposure: the current evidence for the relationship between traumatic experiences and spirit possession

Abstract: BackgroundWe present a literature review on trauma exposure and spirit possession in low- and middle-income countries (LMICs). Despite the World Health Organization's objective of culturally appropriate mental health care in the Mental Health Action Plan 2013–2020, and the recommendations of the Inter-Agency Standing Committee to consider local idioms of distress and to collaborate with local resources, this topic still receives very little attention. Pathological spirit possession is commonly defined as invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 48 publications
0
26
0
3
Order By: Relevance
“…Anti-gravitational abilities (i.e., levitation) have also been reported as a rare sign. Large scale recent research in Low and Middle Income Countries (LMIC) has shown that people with a history of childhood abuse or severe trauma are particularly vulnerable (Hecker et al, 2015) as are those who dabble in occult practices (e.g. Ouija boards, cultic groups, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-gravitational abilities (i.e., levitation) have also been reported as a rare sign. Large scale recent research in Low and Middle Income Countries (LMIC) has shown that people with a history of childhood abuse or severe trauma are particularly vulnerable (Hecker et al, 2015) as are those who dabble in occult practices (e.g. Ouija boards, cultic groups, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Rituals to appease the ghost and resolve the internal conflict and feeling of unfulfilled obligation are consequently common and would be added to or replace treatment (105,106) but might be interrupted in war or displacement. Culture specific explanatory models for symptoms or illness must also be considered (111), as symptoms for example of PTSD might be attributed not to torture, but to other including metaphysical problems like witches or spirits (112). Illness behaviour including primary presentation of physical symptoms is common in many cultures and could be argued to be rather a culture based presentation of illness rather than Somatoform Disorder in the common ICD or DSM definition.…”
Section: Understanding the Cultural Background In The Assessment Of Vmentioning
confidence: 99%
“…The relation between traumatic experiences and spirit possession in LMICs is analyzed in a systematic review of 21 articles undertaken by Hecker et al Pathological spirit possession is a phenomenon occurring globally and has particular relevance in LMICs. Reported prevalence rates differed conspicuously depending on cultural background and the particular study populations (Hecker et al, 2015 ), for example, high rates were found in post-war areas, confirming the connection between traumatic experiences and pathological spirit possession.…”
mentioning
confidence: 90%
“…This special issue of the European Journal of Psychotraumatology collected some of the work that has been done so far in LMICs. Manuscripts address important issues such as the quantification of effects of cumulative trauma exposure in war survivors (Wilker et al, 2015 ); factors related to psychological distress in orphans living in Tanzania (Hermenau, Eggert, Landolt, & Hecker, 2015 ); the relationship between trauma exposure and spirit possession (Hecker, Braitmayer, & Van Duijl, 2015 ); trauma-related mental health problems in humanitarian staff (Strohmeier & Scholte, 2015 ); and sociotherapy approach developed and implemented in Rwanda (Jansen et al, 2015 ).…”
mentioning
confidence: 99%